High‐Performance Semitransparent and Bifacial Perovskite Solar Cells with MoOx/Ag/WOx as the Rear Transparent Electrode. Issue 20 (23rd August 2020) - Liang, Fengxia; Ying, Zhiqin; Lin, Yi; Tu, Bao; Zhang, Zheng; Zhu, Yudong; Pan, Hui; Li, Haifeng; Luo, Linbao; Ageev, Oleg; He, Zhubing
Abstract: Semitransparent solar cells play a crucial role in such typical photovoltaic applications as smart windows, transparent chargeable devices, tandem and bifacial devices, and so on. Relying on the commercial conductive transparent oxides as the front electrodes, the development of rear transparent electrode (RTE) is especially essential. Here, an efficient semitransparent perovskite solar cell (PSC) with the softly deposited transparent MoO x /Ag/WO x (MAW) as the rear electrode is demonstrated. MoO x enables the continuously grown silver ultrathin film while the high‐refractive‐index WO x capping layer can modulate the whole optical interference and enhance the light transmission throughout the device. As a result, depending on the MAW RTE, the semitransparent normal planar PSC owns the optimal conversion efficiency of 15.40% along with 10.17% in the average visible‐light transmission (AVT) simultaneously, which claims the best conversion efficiency of the semitransparent PSCs at such considerable AVT. Combining the optical characterizations, the bifacial performance test of the same device also reveals the uneven absorption due to the different optical interference depending on the light direction, as well as the typical parasitic absorption by the functional layers. This paper paves an alternative and promising way to fabricate high‐performance semitransparent optoelectronic devices in the future. Abstract : Softly deposited transparent MoO x /Ag/WO x composite films enable high‐performance semitransparent perovskite solar cells obtaining an optimal conversion efficiency of 15.40% along with 10.17% in the average visible‐light transmission simultaneously.